Epidemiology of Invasive Pulmonary Aspergillosis Among Intubated Patients With COVID-19: A Prospective Study. (28th July 2020) - Bartoletti, Michele; Pascale, Renato; Cricca, Monica; Rinaldi, Matteo; Maccaro, Angelo; Bussini, Linda; Fornaro, Giacomo; Tonetti, Tommaso; Pizzilli, Giacinto; Francalanci, Eugenia; Giuntoli, Lorenzo; Rubin, Arianna; et al.
Abstract: Background: We evaluated the incidence of invasive pulmonary aspergillosis among intubated patients with critical COVID-19 and evaluated different case definitions of invasive aspergillosis. Methods: Prospective, multicenter study in adult patients with microbiologically confirmed COVID-19 receiving mechanical ventilation. All included participants underwent a screening protocol for invasive pulmonary aspergillosis with bronchoalveolar lavage galactomannan and cultures performed on admission at 7 days and in case of clinical deterioration. Cases were classified as coronavirus-associated pulmonary aspergillosis (CAPA) according to previous consensus definitions. The new definition was compared with putative invasive pulmonary aspergillosis (PIPA). Results: 108 patients were enrolled. Probable CAPA was diagnosed in 30 (27.7%) patients after a median of 4 (2–8) days from intensive care unit (ICU) admission. Kaplan-Meier curves showed a significantly higher 30-day mortality rate from ICU admission among patients with either CAPA (44% vs 19%, P = .002) or PIPA (74% vs 26%, P < .001) when compared with patients not fulfilling criteria for aspergillosis. The association between CAPA (OR, 3.53; 95% CI, 1.29–9.67; P = .014) or PIPA (OR, 11.60; 95% CI, 3.24–41.29; P < .001) with 30-day mortality from ICU admission was confirmed, even after adjustment for confounders with a logistic regression model. Among patients with CAPA receiving voriconazole treatment (13 patients; 43%) a trend toward lower mortality (46% vs 59%; P = .30) and reduction in galactomannan index in consecutive samples were observed. Conclusions: We found a high incidence of CAPA among critically ill COVID-19 patients and its occurrence seems to change the natural course of disease. Abstract : Using a prospective surveillance based on galactomannan and cultures on bronchoalveolar lavage in mechanical ventilated patients with COVID-19, we found a high incidence of invasive pulmonary aspergillosis. The occurrence of aspergillosis significantly changes the natural history of the disease.